Optimization of pH and Contact Time of Media in Removing Calcium and Magnesium from Groundwater - Abd Aziz, Nor Izzah (International Journal of Integrated Engineering, 2019)
Biosorption is one of the method which can be used to remove metals and pollutants from groundwater. This study has been conducted to optimize pH and contact time of media in removing the Ca2+ and Mg2+ in groundwater. The media that was used in this study are activated carbon made up from rice husks (RHAC), sands and zeolite. Media characterization using XRF, FTIR and SEM were used to identify the changes in media morphology. The method used in this study is the filtration process which will be done through batch study. In this batch study, the optimum condition of pH and contact time for removal of metals from groundwater are found to be at pH 7 and 60 minutes. All the media that were used in this study were found capable to remove the metals and pollutant in groundwater.